2017
DOI: 10.1016/j.neuron.2017.04.011
|View full text |Cite|
|
Sign up to set email alerts
|

Conditional Deletion of All Neurexins Defines Diversity of Essential Synaptic Organizer Functions for Neurexins

Abstract: Neurexins are recognized as key organizers of synapses that are essential for normal brain function. However, it is unclear whether neurexins are fundamental building blocks of all synapses with similar overall functions, or context-dependent specifiers of synapse properties. To address this question, we produced triple conditional knockout mice that allow ablating all neurexin transcripts in mice. Using neuron-specific manipulations combined with immunocytochemistry, paired-recordings, and two-photon Ca2+-ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
281
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(307 citation statements)
references
References 40 publications
22
281
4
Order By: Relevance
“…Our data confirm previous findings that neurexins are important for presynaptic Ca 2+ ‐channel function (Missler et al , ; Zhang et al , ; Yamashita et al , ; Chen et al , ; Tong et al , ; Brockhaus et al , ), but none of the previous studies defined the actual nature of the observed impairments because direct measurements of presynaptic Ca 2+ ‐fluxes are only possible in calyx synapses. By directly measuring Ca 2+ ‐channel function in patched presynaptic calyx terminals and simultaneously monitoring synaptic vesicle exocytosis, we could show that the pan‐neurexin deletion does not affect voltage‐gated Ca 2+ ‐channels as such, but selectively impairs the coupling of Ca 2+ ‐influx to neurotransmitter release (Figs 3–5).…”
Section: Discussionsupporting
confidence: 87%
“…Our data confirm previous findings that neurexins are important for presynaptic Ca 2+ ‐channel function (Missler et al , ; Zhang et al , ; Yamashita et al , ; Chen et al , ; Tong et al , ; Brockhaus et al , ), but none of the previous studies defined the actual nature of the observed impairments because direct measurements of presynaptic Ca 2+ ‐fluxes are only possible in calyx synapses. By directly measuring Ca 2+ ‐channel function in patched presynaptic calyx terminals and simultaneously monitoring synaptic vesicle exocytosis, we could show that the pan‐neurexin deletion does not affect voltage‐gated Ca 2+ ‐channels as such, but selectively impairs the coupling of Ca 2+ ‐influx to neurotransmitter release (Figs 3–5).…”
Section: Discussionsupporting
confidence: 87%
“…Recent preliminary analyses of triple conditional triple KOs that ablate expression of all α- and β-neurexins extended these results, uncovering dramatic differences in the overall functions of neurexins between different types of synapses (Chen et al, 2017). Deletion of all neurexins from parvalbumin-positive interneurons in the prefrontal cortex caused a loss of synapses (~30%) and a decrease in synaptic strength (~50%), but no impairment in action-potential-triggered Ca 2+ -influx.…”
Section: Neurexins: Form and Functionmentioning
confidence: 93%
“…Deletion of all neurexins from parvalbumin-positive interneurons in the prefrontal cortex caused a loss of synapses (~30%) and a decrease in synaptic strength (~50%), but no impairment in action-potential-triggered Ca 2+ -influx. In contrast, deletion of neurexins from somatostatin-positive interneurons caused no synapse loss, but a large decrease in action-potential-triggered Ca 2+ -influx (~50%) that also suppressed synaptic strength (~50%; Chen et al, 2017). Thus, deletion of neurexins impaired synaptic transmission in two different types of synapses to the same extent, but by different mechanisms, suggesting that neurexins perform distinct regulatory functions in different classes of neurons instead of a canonical regulatory function in all neurons.…”
Section: Neurexins: Form and Functionmentioning
confidence: 93%
See 1 more Smart Citation
“…Here, loss of neurexins in mice reduces excitatory synapse number at select synapses such as climbing fiber inputs to Purkinje cells (Chen et al, 2017) but not in other brain regions (Dudanova et al, 2007). In terms of physiological maturation, neurexins are critical synaptic organizers as first shown in vivo by the result that α-neurexin loss impairs evoked neurotransmission (Missler et al, 2003).…”
Section: Relevant Structures and Their Patterning In The Three Synaptmentioning
confidence: 99%